Formation of professional thinking of the teacher - Turdieva Zebiniso Abdullajon kizi (Zien Journals, 2022)
Development and education sphere updating, and change of system and character of vocational training of teacher act as an overall objective and means of social and economic and spiritual progress of our developed and modern society. Only the highly skilled and competent experts possessing potential possibilities to create and develop in new and modern conditions of life who differ nonconventional style of the scientific and pedagogical thinking, able competently to solve professional problems, are capable to form pedagogical reality and to reach effective results. Professional level of experts can be caused development of professional thinking and can become result of the purposeful organization of system of formation of thinking of the future teachers on a scientific and pedagogical basis which are carried out within all years of training in pedagogical high school.
Keywords: Education spheres; social and economic progress; spiritual progress; scientific and pedagogical thinking